The Discourse Of Informal Education: Developing Children Characters During Covid-19 Pandemic - Ida Bagus Brata; Ida Bagus Nyoman Mantra; Ida Bagus Rai; Ida Bagus Nyoman Wartha (Denpasar Institute, 2021)
Parents are the first and foremost educators in the process of child development by positioning the house into a multipurpose building full of meaning. This study aims to explore the discourse of informal education in building children's character during the coronavirus disease-19 (covid-19) pandemic. This study is descriptive-qualitative. Data collection was carried out by studying documents and literature. The results of the study showed that the emergence of Covid-19 was initially responded to normally like other viruses, but the increasing number of victims eventually caused panic which affected the socio-cultural community, Covid-19 forces people to work and stay at home more. Social interaction, face-to-face communication and being replaced online by taking advantage of the sophistication of technology, and the role of parents is important by placing the family as one of the pillars of education to instill the norms, morals, and rules of conduct in consistently carrying out the government programs to prevent and break the chain of covid-19 transmission